Sartorial politics in early modern Europe
1 online resource (344 pages).
Keywords: For women at the early modern courts, clothing and jewellery were essential elements in their political arsenal, enabling them to signal their dynastic value, to promote loyalty to their marital court and to advance political agendas. This is the first collection of essays to examine how elite women in early modern Europe marshalled clothing and jewellery for political ends. With essays encompassing women who traversed courts in Denmark, England, France, Germany, Habsburg Austria, Italy, Portugal, Spain and Sweden, the contributions cover a broad range of elite women from different courts and religious backgrounds as well as varying noble ranks.